Production Of Antimicrobial Compounds From A Local Marine Bacterial Isolate, Bacillus Sp.(S1A4) [QR82.B3 L732 2007 f rb]. - Lim, Hui Ming (2007)

(untitled)
A total of 160 strains of marine microorganisms were supplied by the Fisheries Research Institute, Penang. They were collected and isolated from samples all over the shores of Malaysia.